ANALISIS KESEHATAN BANK MENGGUNAKAN METODE RISK PROFILE, GOOD CORPORATE GOVERNANCE, EARNING DAN CAPITAL BANK PERKREDITAN RAKYAT - Christrisia, Christrisia; Marlina Br. Purba, Neni (Aksara Public, 2020)
This study aims to determine Bank Health Analysis Using Risk Profile, Good Corporate Governance, Earning and Capital Methods in Rural Credit Banks in Financial Services Authority in 2014-2018. This research uses qualitative approach, sources of documentation data and downloads from official website of Financial Services Authority. Type of data used is secondary data. Population in this study are 27 BPR in Batam City. Sampling was done by purposive sampling method so the samples obtained are 16 BPR. Analysis method used is risk profile measured by the ratio of Non Performing Loans, Good Corporate Government measured using managerial ownership. Earning measured by Return On Assets and Capital measured by Capital Adequacy Ratio. Based on results of analysis, this research shows that during 2014 to 2018 BPRs registered with Financial Service Authority Batam City get an average rating of 1 or very healthy. Non Performance Loan ratio calculation illustrates banks manage non-performing credit risk well. Good Corporate Governance evaluation shows that management of company has been running well. Return on Asset calculation shows ability of BPR to achieve high profits. Capital Adequacy Ratio calculations above minimum limit of Bank Indonesia are considered able to manage their capital.